Construction of the Paradigm of Islamic Universality in Maḥmūd Shaltūt's Taqrīb Madhāhib Project - Zainal Fanani (An-Nur International Journal of Islamic Thought, 2023)
This paper will discuss the universality of Islam in the thought of Maḥmūd Shaltūt. The universality of Islam is an essential topic amid a crisis in the meaning of Islam due to violent conflicts that are often in the name of Islam. As a result, Islam, which is known to have a vision of raḥmatan li al-‘ālamīn, is perceived as a religion that legalizes violence for the sake of group interests. Maḥmūd Shaltūt is a moderate figure who tries to define Islam in a universal, moderate, and tolerant manner. This paper will explain Maḥmūd Shaltūt's biography based on a literature study. Then, it is directed to explain Islam in the distinction between the meaning of Aqidah and Sharia, followed by explaining the construction of the paradigm of Islamic universality through Mahmud Maḥmūd Shaltūt's interpretation of the word Islam in the Qur’an. The final part will review the implementation of Maḥmūd Shaltūt's paradigm of Islamic universality in the discourse of taqrīb madhāhib. This paper finds that (1) the crisis in the interpretation of Islam begins with the issue of the distinction between the meaning of aqidah and sharia. (2) in Maḥmūd Shaltūt's thought, Islam's universality comes from the Qur’an's universality. (3) the universality of Islam explored through the interpretation of the Qur’an led Maḥmūd Shaltūt to an understanding of Islam in the theological and sociological realms. Based on the paradigm of Islamic universality, Maḥmūd Shaltūt implemented the principle of Islamic universality in the discourse of taqrīb bayna madhāhib.